2016
DOI: 10.1002/prca.201500071
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of eccrine sweat reveals its potential as a diagnostic biofluid for active tuberculosis

Abstract: Proteomics of sweat from active TB patients is a viable approach for biomarker identification, which could be used to develop a nonsputum-based test for detection of active TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…We observed a similar pattern as highlighted by glutaredoxin‐1, peroxiredoxin‐1, and quiescin sulfhydryl oxidase 1 (Figure C and Table S1, Supporting Information). In addition, the detection of membranous, cytoskeletal, microsomal, mitochondrial, ribosomal, and nuclear proteins in eccrine sweat support the hypothesis that proteins are secreted into sweat in a merocrine‐like manner, including abundant defense proteins, such as, apolipoprotein D, dermcidin, and prolactin‐inducible protein . Our results confirm the findings of these previous studies and support the conclusion that these collection methods provide material representative of sweat proteomes.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We observed a similar pattern as highlighted by glutaredoxin‐1, peroxiredoxin‐1, and quiescin sulfhydryl oxidase 1 (Figure C and Table S1, Supporting Information). In addition, the detection of membranous, cytoskeletal, microsomal, mitochondrial, ribosomal, and nuclear proteins in eccrine sweat support the hypothesis that proteins are secreted into sweat in a merocrine‐like manner, including abundant defense proteins, such as, apolipoprotein D, dermcidin, and prolactin‐inducible protein . Our results confirm the findings of these previous studies and support the conclusion that these collection methods provide material representative of sweat proteomes.…”
Section: Resultssupporting
confidence: 79%
“…Adewole et al. demonstrated that 26 proteins were uniquely detected in pooled sweat samples from patients with active tuberculosis . However, few studies have performed a broad, quantitative analysis of antibody isotypes and cytokines in individual sweat samples from healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Although some diseases can be diagnosed by measuring only one biomarker (such as glucose for diabetes, 70 lactate or NH4 + for fatigue due to anaerobic exercise, 69,[71][72][73] and Clfor cystic fibrosis), 74 recent omics analyses have revealed that most diseases should be carefully diagnosed by simultaneously measuring the change of multiple biomarkers in sweat. 77,[81][82][83][84] Hence, basic operational principles of sensors for sweat biomarkers should be based on highly-selective biorecognition reaction with reference to the conventional enzyme-based blood glucose sensors that utilize enzyme-modified Clark-type oxygen sensor electrodes. 85 Integration of multiple biosensing elements into one chip enables the fabrication of biosensor arrays in a portable form.…”
Section: Sweat Biomarkers and Their Collection/ Detection Techniquesmentioning
confidence: 99%
“…With recent advances in analytical as well as sweat sampling technology, the composition of sweat has been further characterized, and it is now known to contain a much larger spectrum of molecules, including proteins, carbohydrates, organic acids, lipids, and lipid-derived metabolites (48). Correspondingly, the potential applications of sweat for diagnostic purposes have increased, including speculations that the sweat proteome may be useful for the diagnosis of infections, and psychiatric and neoplastic diseases (7, 9, 10). It should be noted that the vast majority of these studies characterized the composition of eccrine sweat, which is produced from sweat glands located throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Correspondingly, the potential applications of sweat for diagnostic purposes have increased, including speculations that the sweat proteome may be useful for the diagnosis of infections, and psychiatric and neoplastic diseases. 7,9,10 It should be noted that the vast majority of these studies characterized the composition of eccrine sweat, which is produced from sweat glands located throughout the body. Apocrine and apoeccrine sweat glands located in the axillary and genital regions of the body have a distinct secretory mechanism from eccrine sweat glands, and apocrine and apoeccrine sweat are less well-characterized compared to eccrine sweat.…”
mentioning
confidence: 99%